The Application of Learning Method Using Snowball Throwing Game in Grade 2 SDN Sumberwuluh 03 - Pramesti, Reghina; Mamang, Siti Maryam; Sari, Suci Anjar; Listiani, Halida (Talenta Publisher, 2023)
The educational internship activity carried out in Lumajang aims to carry out general tasks in the educational internship program and help normalize learning activities in two schools that have been affected by the eruption of Mount Semeru which occurred last December. This educational internship is useful for increasing student participation in honing their abilities as prospective teachers in accordance with their respective fields of knowledge. In the process of learning activities in grade 2 of SDN Sumberwuluh 03, the snowball throwing game method is used to practice interrogative communicative skills and students' skills. The application of learning activities with the game method is expected that students can be more active, creative and enthusiastic in carrying out learning activities. Students are expected to be more responsive and alert when doing school assignments, as well as train students to be more responsive in answering during learning activities. The results of the application of the snowball throwing learning method have a positive impact. This can be seen in the students' reading and writing abilities which have increased. Suggestions for teachers and prospective teachers to further optimize learning activities with various fun methods, especially for low grade education.